Results of treatment of cancer patients with peritoneal carcinomatosis - Bondar, O.; Rybin, A.; Varabina, A. (Journal of Education, Health and Sport, 2022)
Objective: At present, common forms of cancer of different localization can not be ignored. New approaches to the treatment of metastatic lesions have some success in clinical application. This study is devoted to the experience of using the technology of cytoreductive surgery and hyperthermic intraoperative intraperitoneal chemotherapy (HIPEC) in practice, as well as the analysis of overall and relapse-free survival in the examined groups of patients. Patients and methods: A total of 119 people were recruited from 2013 to 2020 inclusive. Patients were divided into two groups: the clinical control group (n = 53) consisted of individuals who underwent suboptimal cytoreduction; in the main group (n = 66) there were patients who performed optimal or complete cytoreductive volume and in some cases underwent intraoperative hyperthermic chemotherapy. Patients diagnosed with stage IIIC ovarian cancer were treated. In the initial analysis of these groups, time indicators (period before surgery, duration of surgery, number of postoperative bed-days), as well as the presence and nature of complications in the postoperative period were taken into account. Results: The analysis showed an increase in relapse-free survival from 10 months in the control group to 13-19 months in the main group, also significantly increased (from 5 to 22%) the number of complications of class III-IV in HIPEC. Conclusion: The study is prospective and retrospective, recruitment into groups has been conducted since 2013. Observation of the studied groups continues. The expected results will be a significant discrepancy between overall and recurrence-free survival in the study groups.